Formation of Students' Character Through Artistic Traditions Didong - Mahyuddin, Mahyuddin; Fitrah, Hariki; Muharramsyah, Rambang (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
The character problem of students is a problem that must be resolved in order to give birth to a generation of people who have good morals and character. The aim of this research is to explore the art of didong in forming the character of students at the Atu Lintang 7 Elementary School. This research is qualitative research using an ethnographic approach. The informants in this research were school principals, teachers and artists. The technique for taking informants uses snowball sampling technique. Data was collected through observation, interviews and documentation. Data analysis techniques use domain analysis, componential analysis, taxonomic analysis and cultural theme analysis. To ensure the validity of the data, triangulation is used. The results of the research show that the formation of students' character through didong arts is carried out through extracurricular activities. Some of the character values ​​contained in Didong art are religious values, discipline values, mutual cooperation values, discipline values ​​and responsibility values.